The Conserved Tyr176/Leu177 motif in the alpha-Helix 9 of the feline immunodeficiency virus capsid protein is critical for gag particle assembly - Ovejero, César Antonio (2019)
The capsid domain (CA) of the lentiviral Gag polyproteins has two distinct roles during virion morphogenesis. As a domain of Gag, it mediates the Gag–Gag interactions that drive immature particle assembly, whereas as a mature protein, it self-assembles into the conical core of the mature virion. Lentiviral CA proteins are composed of an N-terminal region with seven α-helices and a C-terminal domain (CA-CTD) formed by four α-helices. Structural studies performed in HIV-1 indicate that the CA-CTD helix 9 establishes homodimeric interactions that contribute to the formation of the hexameric Gag lattice in immature virions. Interestingly, the mature CA core also shows inter-hexameric associations involving helix 9 residues W184 and M185. The CA proteins of feline immunodeficiency virus (FIV) and equine infectious anemia virus (EIAV) exhibit, at equivalent positions in helix 9, the motifs Y176/L177 and L169/F170, respectively. In this paper, we investigated the relevance of the Y176/L177 motif for FIV assembly by introducing a series of amino acid substitutions into this sequence and studying their effect on in vivo and in vitro Gag assembly, CA oligomerization, mature virion production, and viral infectivity. Our results demonstrate that the Y176/L177 motif in FIV CA helix 9 is essential for Gag assembly and CA oligomerization. Notably, mutations converting the FIV CA Y176/L177 motif into the HIV-1 WM and EIAV FL sequences allow substantial particle production and viral replication in feline cells.